Strategi Menghafal Al-Qur’an di SMPU BP Amanatul Ummah Pacet Mojokerto - Moh. Ismail; Waridatul Husnawiyah Ruqoyah (Intizam, Jurnal Manajemen Pendidikan Islam, 2022)
Amanatul Ummah Junior High School has a superior program for memorizing the Koran at least 9 chapters using a unique strategy. This study aims to present a strategy for memorizing the Koran at SMPU BP Amanatul Ummah and to find the supporting and inhibiting factors of this memorization strategy. The research method used is a qualitative approach with a case study type of research. The data obtained through three techniques, namely: observation, interviews and documentation. Based on the research results, it is known that the strategies for memorizing the Koran at Amanatul Ummah Pacet Mojokerto Junior High School are as follows: a) Growing and developing students' talents in memorizing the Koran b) Forming a team of tahfidz teachers with the title hafidz hafidzah. c) Improving and perfecting the management of tahfidz al-Qur'an d) Improving mechanisms and methods e) There will be graduations for those who meet the minimum target of 9 juz and f) Evaluation. Second. Supporting and inhibiting factors in memorizing the Koran at Amanatul Ummah Pacet Mojokerto Junior High School. For the supporting factors, namely: 1) There is self-awareness from students. 2) Perseverance and intelligence of students in memorizing the Qur'an 3) There is encouragement and motivation from family, parents and relatives. 4) Choose the right time to memorize the Qur'an. 5) Being under the auspices of the Amanatul Ummah Islamic boarding school. As for the inhibiting factors, namely: 1) Lack of motivation and attention from family, parents and teachers. 2) Inadequate infrastructure facilities. 3) Laziness and lack of awareness in students in memorizing the Qur'an. 4) The atmosphere is not conducive.